Pendekatan Konseling Pastoral sebagai Solusi dalam Mengatasi Kecemasan - Clarine, Michelle; Hidradjat, Juliana (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Anxiety is a significant mental health issue that affects the emotional, mental, and spiritual well-being of individuals, including church members. This study aims to develop an integrated pastoral counseling model to assist congregants in addressing anxiety holistically by combining psychological principles with Christian values based on the Bible. The research employs a qualitative methodology through library research, drawing from theological, psychological, and pastoral counseling literature. The findings indicate that pastoral counseling plays a pivotal role in providing emotional and spiritual support through emotional healing, sustaining individuals during challenging times, guiding decision-making, and reconciling relationships with God, others, and oneself. This approach not only alleviates symptoms of anxiety but also strengthens the faith and spiritual connection of congregants with God. The church serves as a healing community that offers a safe environment for sharing, spiritual reflection, and faith reinforcement. The study concludes that pastoral counseling based on the integration of theology and psychology can be an effective solution for addressing anxiety, reducing mental health stigma, and enhancing the holistic quality of life for congregants. The designed model offers practical guidance for churches to train leaders and pastoral counselors in supporting the emotional and spiritual well-being of their members.